Insilico screening of biocomponents in cympobogan citratus and allium sativum against microsporum sp - G. KRISHNAVENI,; DR. E. M. RAJESH, (International Journal of Pharma and Bio Sciences, 2017)
Effective and nontoxic antifungal agents are required for the treatment of dermatophytosis. Plants and their extracts have been used as medicines against superficial infections. In our present study, from the Leaves of Cymbopogon citratus (lemon grass) and pulp of Alllium sativum (garlic) extracts were prepared by using different solvent i.e., Ethanol, Ethyl acetate, Chloroform and Aqueous extract using soxhlet apparatus and to investigate the antifungal activity. Water Samples were collected from sewage, swimming pools and lakes in Chennai, Tamilnadu. Microsporum gypseum and Microsporum canis were isolated and identified from the samples. Phytochemicals analysis with the Leaves of Cymbopogon citratus (lemon grass) and pulp of Alllium sativum (garlic) extracts were studied using different solvent i.e., Ethanol, Ethyl acetate, Chloroform and Aqueous extract MIC and MFC were carried out with the isolates, Cymbopogon citratus extract with Ethyl acetate showed higher antidermatophytic activity, by inhibiting the Microsporum canis at the concentration of 62.5(µg/ml), and Ethanolic extracts the concentration of 125(µg/ml) and aqueous extract in the concentration of 500(µg/ml). Alllium sativum extract with Ethyl acetate showed higher antidermatophytic activity,by inhibiting the Microsporum gypseum at the concentration of 62.5(µg/ml), and chloroform extract in the concentration of 250(ug/ml) and aqueous extract in the concentration of 1000(µg/ml). Gas Chromatography Mass Spectroscopy was done to identify the biochemical peak components and the activities present in the Cymbopogon citratus and Alllium sativum extracts. Seven compounds were identified with their following retention time. Citral (18.83), dimethyl sulfide (19.58) followed by nonadeconic acid (20.87), Brassidic acid (21.87), Behenic acid (22.82), hexodeconic acid (17.17) and Flavone (14.07). of which Flavone, citral and dimethyl sulphide acts as the ligands to bind with the specific proteins present in the organism and to have inhibitory activity. Molecular docking was done for the LAP1 protein and MEP1 proteins from Microsporum sp. Citral compound found to have greater inhibitory property against the pathogenic dermatophytes. Ethyl acetate extracts of Cymbopogon citratus and Alllium sativum have medicinal property to treat infectious pathogenic fungi.